Representations of Autism and Autism Spectrum Disorder (ASD) in the North American Roman Catholic Print Media, 1990-2013 - Sawchuk, Dana (Journal of disability & religion, 2015)
This article is a qualitative content analysis of how autism and autism spectrum disorder are portrayed in the North American Roman Catholic print media. The findings suggest that there is an absence of medicalization and scientific explanations for the disorder in the magazines and newspaper analyzed. Instead, these publications stress the acceptance and inclusion of individuals with autism spectrum disorder and a celebration of their differences. The themes found in these Catholic publications differ dramatically from those found in mainstream secular magazines, which tend to approach children's developmental issues from a biomedicalized and risk society perspective that emphasizes intensive mothering.